1999
DOI: 10.1046/j.1523-1755.1999.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term protective effect of UR-12670 after warm renal ischemia in uninephrectomized rats

Abstract: The chronic administration of the PAF antagonist UR-12670 attenuates the long-term effects of ischemia-reperfusion injury in uninephrectomized rats. The beneficial effect of this agent, even when given beyond the initial ischemia/reperfusion injury, suggests that PAF plays a role in the mechanisms of progression to late renal damage in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…This is in accordance with previous studies that showed, in isolated perfused rat kidney, that the addition of PAF induced proteinuria, at similar levels to that induced by angiotensin II. 35 In addition, Torras et al 36 showed that longterm pharmacological blockade of PAFR protects from progressive renal injury. On the other hand, another work did not observe any difference concerning albuminuria levels between animals treated or not with PAFR antagonist in the ablation model of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies that showed, in isolated perfused rat kidney, that the addition of PAF induced proteinuria, at similar levels to that induced by angiotensin II. 35 In addition, Torras et al 36 showed that longterm pharmacological blockade of PAFR protects from progressive renal injury. On the other hand, another work did not observe any difference concerning albuminuria levels between animals treated or not with PAFR antagonist in the ablation model of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…si on in jury to the he art musc le, 19 a pro tec ti on against isc he mic in jury to the kid ney, 20 a re duc ti on of the isc he mi a-re per fu si on da ma ge to the lung, 21 and an ame li o ra ti on of the isc he mi a-re per fu si on in jury to the li ver. 22 The se re sults ha ve led us to at tempt to tre at ment by a PAF an ta go nist ABT-491 in models of HI.…”
Section: Fi Gu Rementioning
confidence: 99%
“…9 Treatment with several PAF antagonists has been reported in acute renal failure 10 and chronic renal failure animal models. 11,12 However, problems exist regarding the lack of specificity of PAF antagonists. [13][14][15][16] Therefore, we have developed genetically engineered PAFR-deficient (PAFR-KO) mice to confirm the role of PAF in vivo.…”
mentioning
confidence: 99%